Human exposure to dioxins through diet in Italy - Taioli, E.; Marabelli, R.; Scortichini, G.; Migliorati, G.; Pedotti, P.; Cigliano, A.; Caporale, V. (Chemosphere (Oxford), 2005)
We have measured the content of polychlorinated dibenzo- p-dioxins, and polychlorinated dibenzofurans (together defined as “dioxins”) in 269 samples of food of animal origin collected through the regional veterinary services, covering the national territory. Quantification of the dioxins was accomplished by isotope dilution method, and toxic equivalents (TEQ) were calculated. The average daily food intake was obtained from two main sources: national data collected by the National Institute of Nutrition, and data from an ongoing cohort study on diet and cancer including 40, 000 Italian subjects. The mean value of dioxins measured in food of animal origin was 0.144 ± 0.266 pg-TEQ/g (range: 0.003–1.655 pg-TEQ/g). Fish was the item with the highest content. The estimated intake of dioxins with main food items of animal origin is presented. The major contribution to dioxins intake with food comes from cow milk and fish consumption. These results are in agreement with what observed in studies conducted in other countries, such as Germany, Finland, Japan, Spain, and are below the limits set by the European legislation.